From Classroom to Marketplace: Empowering Business English Students with Cross-Border Product Digital Storytelling - Yu, Yanshen; Deng, Ning; Xu, Manting; Liang, Shiyan (Journal of Research in Vocational Education, 2024)
Although many studies have examined the potential of digital storytelling in higher education, few have investigated its application in Business English teaching at a micro-level. This study explores how digital storytelling, particularly through cross-border livestream simulations, can enhance Business English teaching by integrating language learning with essential business skills. Qualitative data, derived from in-depth interviews, classroom observations, field notes, students’ product stories, reflective journals, teaching logs and teaching documents, were collected and analyzed, revealing some key competences such as live-stream skills, collaboration, critical thinking, digital literacy, and language communication, were developed finely in the course. The findings suggest that digital storytelling, underpinned by ESP and CLIL pedagogies, enriches the learning experience and prepares Business English students for evolving global market by upgrading their skill set.